Line-Scan Raman Microspectrometry for Biological Applications - De Grauw, C. J.; Otto, C.; Greve, J.
developed for the study of biological samples such as cells and chromosomes. With the illumination of a line on the sample, all the spectral information of the line is recorded. The line-scan microscope was attained by the introduction of one scanning mirror, a slit, and two cylindrical lenses in a standard confocal Raman microscope. The resolu tion, for an ideal sample, is 0.5 m m in the lateral direction and 3.5 m m in the axial direction. Line-scan experiments were performed to demonstrate the applicability of the instrument for biological samples. Line-scan images of calcium phosphate bone implant coatings and of the banding pattern of polytene chromosomes are presented.
Keywords: RAMAN; MICROSCOPY; RESOLUTION; LINE ILLUMINATION